Electronic instruments and instrumentations technology - Anand, M.M.S. (New Delhi : Prentice Hall of India, 2006)
Engeering
Keywords: Electronics; Instrument and accessories; Analog metres; Digital metres; Bridge instruments; Signal generators; Signal analysis; Metrology; Industrial communication techniques